Endoscopic outcomes using a novel through-the-scope tack and suture system for gastrointestinal defect closure: a systematic review and meta-analysis - Canakis, Andrew; Deliwala, Smit S.; Frohlinger, Michael; Twery, Benjamin; Canakis, Justin P.; Shaik, Mohammed Rifat; Gunnarsson, Erik; Ali, Osman; Dahiya, Dushyant Singh; Gorman, Emily; Irani, Shayan S.; Baron, Todd H. (Endoscopy, 2024)
Background Closure of gastrointestinal defects can reduce postprocedural adverse events. Over-the-scope clips and an over-the-scope suturing system are widely available, yet their use may be limited by defect size, location, operator skill level, and need to reinsert the endoscope with the device attached. The introduction of a through-the-scope helix tack suture system (TTSS) allows for closure of large irregular defects using a gastroscope or colonoscope, without the need for endoscope withdrawal. Since its approval 3 years ago, only a handful of studies have explored outcomes using this novel device.Methods Multiple databases were searched for studies looking at TTSS closure from inception until August 2023. The primary outcomes were the success of TTSS alone and TTSS with clips for complete defect closure. Secondary outcomes included complete closure based on procedure type (endoscopic mucosal resection [EMR], endoscopic submucosal dissection [ESD]) and adverse events.Results Eight studies met the inclusion criteria (449 patients, mean defect size 34.3 mm). Complete defect closure rates for TTSS alone and TTSS with adjunctive clips were 77.2% (95%CI 66.4–85.3; I2=79%) and 95.2% (95%CI 90.3–97.7; I2=42.5%), respectively. Complete defect closure rates for EMR and ESD were 99.2% (95%CI 94.3–99.9; I2 = 0%) and 92.1% (95%CI 85–96; I2=0%), respectively. The adverse event rate was 5.4% (95%CI 2.7–10.3; I2=55%).Conclusion TTSS is a novel device for closure of postprocedural defects, with relatively high technical and clinical success rates. Comparative studies of closure devices are needed.